Knockdown of interleukin-1 receptor 1 is not neuroprotective in the 6-hydroxydopamine striatal lesion rat model of Parkinson's disease. (2nd January 2015) - Walsh, Sinéad; Gavin, Aisling; Wyatt, Séan; O'Connor, Catriona; Keeshan, Karen; Nolan, Yvonne M.; O'Keeffe, Gerard W.; Sullivan, Aideen M.
<x xml:space="preserve">Abstract</x> It is well established that neuroinflammation is associated with the progression of many neurodegenerative diseases, including Parkinson's disease (PD). Activated microglia and elevated levels of pro-inflammatory cytokines such as interleukin-1β (IL-1β) have been found in the brain and cerebrospinal fluid of PD patients, suggesting that IL-1β may be involved in the pathogenesis of this disease. This study aimed to knock down the expression of the interleukin-1 type 1 receptor (IL-1R1) to evaluate any potential therapeutic effect of limiting the action of IL-1β in the substantia nigra following a unilateral intrastriatal 6-hydroxydopamine (6-OHDA) lesion in rats. Adult Sprague-Dawley rats received intranigral injections of shRNA specific for IL-1R1, followed 2 weeks later by intrastriatal 6-OHDA. Injection of IL-1R1 shRNA did not prevent 6-OHDA-induced loss of motor function or loss of nigral dopamine neurons. IL-1R1 expression was increased in the midbrain following 6-OHDA injection; this effect was attenuated in 6-OHDA-treated animals that had received IL-1R1 shRNA. These data suggest that while IL-1R1 was increased in 6-OHDA-treated animals and reduced following shRNA injection, the neurodegeneration induced by 6-OHDA was not mediated through IL-1R1.